Mereda Konflik; Menghargai Identitas (studi kasus pada aliran-aliran kepercayaan yang ada di Indramayu) - Khaerul Umam (Lembaga penelitian dan Pengembangan Masyarakat (LPPM) IAIN Kediri, 2018)
The existence of schools’ belief is often seen as the others, whose presence is underestimated, even eliminated. Both through persecution and using state power to pressure them on behalf of the majority. Using a field approach as well as various official reports from the government and mass media coverage, this article explains the existence of religious schools in Indramayu Regency after the issuance of the MUI and Pakem Decree regarding the existence of them as an organization deemed heretical. This deafness comes to the discovery that differences in beliefs are natural in the dynamics of life. Bad stigma attached to different parties, born and developed because of unilateral information without trying to do tabayyun (clarification) to the intended party. Dialogical dialogue is an effective step in reducing conflict with a religious background, to equally respect each other's choices without having to force or use violence.